Adsorption of acetic acid on ion exchange resin in aqueous and non-aqueous conditions: batch equilibrium study and thermodynamic analysis. Issue 4 (8th August 2022) - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Bankar, Sandip B.; Chavan, Prakash V.
ABSTRACT: Adsorptive removal of acetic acid from aqueous and non-aqueous solutions was carried out using strong base anion exchange resin at 303, 313, and 323 K. The effect of concentration of acetic acid, nature of solvent, and temperature on adsorption of acetic acid and swelling of the resin were investigated. Adsorption of acetic acid and swelling of the resin were favoured in non-polar solvents for a given temperature. Adsorption of acetic acid was favoured at 303 K and decreased with an increase in temperature. Langmuir isotherm model was fitted to equilibrium adsorption data to determine the Langmuir adsorption constant and saturation capacity of the resin. Further, thermodynamic parameters viz . ΔG O, ΔH O, and ΔS O were estimated. The negative values of ΔG O and ΔH O showed that the adsorption of acetic acid on the resin was spontaneous and exothermic in nature. GRAPHICAL ABSTRACT: UF0001